The Resources of Religious Humanitarianism: The Case of Migrants on Lampedusa. (5th February 2019) - Rees, John; Rawson, Stefania
Abstract : In the contemporary flow of irregular migrants worldwide, the predicaments of humanitarian work have become a source of public controversy and political disputation. Situated in the discourse of religion in international relations (IR), this introductory article considers conduct available to religious actors in response to the humanitarian challenge. Drawing on the case of refugees reaching the Italian territory of Lampedusa, the article offers a consideration of Pope Francis' visit to the island in 2013 via two interpretive modes of IR postsecularism. This approach, we argue, highlights the value of postsecular IR frameworks to interpret different dimensions of religious agency and to understand the unique resources available to religious actors in humanitarian advocacy.